The Role and Importance of SGLT-2 Inhibitors in Cardioprotection (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores the emerging role of SGLT-2 inhibitors beyond their established use in diabetes management, focusing on their potential cardioprotective effects. SGLT-2 inhibitors, known for their ability to reduce glucose reabsorption in the kidneys, have shown promising impacts on cardiovascular health. By lowering blood glucose levels and blood pressure, they alleviate the workload on the heart, potentially improving cardiac structure and function. Moreover, their anti-inflammatory and antioxidant properties may further contribute to reducing cardiovascular risk. This annotation reviews current research on how SGLT-2 inhibitors influence heart failure and myocardial infarction outcomes, highlighting their dual benefits in managing both diabetes andcardiovascular diseases